Sistem Pendukung Keputusan Pemilihan Jurusan Di SMA Muhammadiyah 4 Kota Bengkulu Menggunakan Metode Saw - Elda Ranisa; Kirman Kirman (Jurnal Media Infotama, 2022)
In choosing a major at Muhammadiyah Public High School (SMA) Bengkulu City, there are several factors to consider. This assessment is carried out in several stages, namely National Examination (UN) scores, Competency Test scores, and Color Blindness Test scores. In this case, the purpose of building a decision support system is to determine student majors according to their abilities using the Simple Additive Weighting (SAW) method. Where the assessment criteria of students are compared with one another so as to produce a decision support system that provides an assessment in the selection of students in choosing majors. The decision support system helps in determining majors, making it easier to make decisions related to the selection of majors by using the Simple Additive Weighting (SAW) method, so that students get majors that match their competencies.